2018
DOI: 10.1002/path.5104
|View full text |Cite
|
Sign up to set email alerts
|

The iron chelator deferasirox synergises with chemotherapy to treat triple‐negative breast cancers

Abstract: To ensure their high proliferation rate, tumor cells have an iron metabolic disorder causing them to have increased iron needs, making them more susceptible to iron deprivation. This vulnerability could be a therapeutic target. In breast cancers, the development of new therapeutic approaches is urgently needed for patients with triple-negative tumors, which frequently relapse after chemotherapy and suffer from a lack of targeted therapies. In this study, we demonstrated that deferasirox (DFX) synergises with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Synergism between the iron chelator, DFX, and conventional cytotoxic chemotherapeutics ( e.g. , doxorubicin, cyclophosphamide, and cisplatin or carboplatin) in the treatment of triple-negative breast cancers has previously been reported [39]. Therapeutic targeting of iron metabolism for breast cancer treatment was reported many years ago [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Synergism between the iron chelator, DFX, and conventional cytotoxic chemotherapeutics ( e.g. , doxorubicin, cyclophosphamide, and cisplatin or carboplatin) in the treatment of triple-negative breast cancers has previously been reported [39]. Therapeutic targeting of iron metabolism for breast cancer treatment was reported many years ago [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…DFX was effective against leukemia cells in preclinical studies and because leukemia patients receive repeated blood transfusions, DFX offers a dual benefit as an anti-cancer agent and treatment for iron overload complications. Additionally, DFO and DFX are effective in preclinical studies of pancreatic (193), breast (194), liver (183), gastric (195), and esophageal (196) cancers, and because they are well-characterized they are often used as positive controls for the study of other iron modulators. Despite promising preclinical results, a pilot study of DFX in advanced hepatocellular carcinoma patients found doselimiting toxicities and the majority (4/5) of the patient tumors progressed while on treatment, therefore the efficacy of DFX for the treatment of solid tumors remains questionable (183).…”
Section: Iron Chelationmentioning
confidence: 99%
“…Recent research published by Yujing et al, (2018) has revealed the protective role of Deferoxamine in leukemic cell apoptosis by regulating the concerned genes. Iron chelators have also been reported to exert anti-proliferative effects in various cancers, including head and neck , colorectal (Cao et al, 2018) and breast (Bajbouj et al, 2018;Tury et al, 2018). Mitoxantrone is a well-known antitumor antibiotic used for the treatment of relapsed acute lymphoblastic leukemia (ALL) (Parker et al, 2010), acute myeloid leukemia (AML), breast cancer, non-Hodgkin's lymphoma, and hormone therapy failed advanced prostate cancer (Shenkenberg and Von Hoff, 1986).…”
Section: Discussionmentioning
confidence: 99%